2016
DOI: 10.4148/2470-6353.1005
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teacher Candidates for the Instruction of English Language Learners

Abstract: This inquiry utilizes a sheltered instruction approach to lesson planning with the intention of improving teacher candidates' instruction to English Language Learners (ELLs). In this study a web-based questionnaire and a sheltered instruction lesson plan template were used to facilitate opportunities for teacher candidates to reflect on and practice planning English for Speakers of Other Languages (ESOL) instruction. Data collections used were nine web-based questionnaire responses and thirty sheltered instruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
(17 reference statements)
0
1
0
Order By: Relevance
“…Projections have indicated that by the year 2025, ELLs will account for 25% of students in public schools (Musu-Gillette et al, 2017). The number of ELLs has exceeded the number of teachers certified to educate the subgroup (National Assessment of Educational Progress [NAEP], 2017), leaving general education teachers responsible for educating ELLs and non-ELLs (Gonzá lez, 2016). Increases in the ELL population have correlated to changes in educational policies on how general education teachers deliver instruction for culturally and linguistically diverse learners.…”
Section: Introductionmentioning
confidence: 99%
“…Projections have indicated that by the year 2025, ELLs will account for 25% of students in public schools (Musu-Gillette et al, 2017). The number of ELLs has exceeded the number of teachers certified to educate the subgroup (National Assessment of Educational Progress [NAEP], 2017), leaving general education teachers responsible for educating ELLs and non-ELLs (Gonzá lez, 2016). Increases in the ELL population have correlated to changes in educational policies on how general education teachers deliver instruction for culturally and linguistically diverse learners.…”
Section: Introductionmentioning
confidence: 99%